Transformasi Perpustakaan Berbasis Inklusi Sosial Studi Kasus: Perpustakaan Universitas Islam Negeri Sunan Kalijaga - Hridyananda, Gede Rai; Ginting, Richard Togaranta; Kawitri Resen, Putu Titah (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2020)
ABSTRACT This final project writing aims to find out the transformation of libraries based on social inclusion in UPT Sunan Kalijaga State Islamic University Yogyakarta. This Research uses descriptive qualitative method. Data collection techniques used are observation to the library, conducting interviews, documentation and literature study. The informant of this study was the Head of the Sunan Kalijaga State Islamic University Yogyakarta Library. The Result of this study aim to determine the transformation of inclusion-based libraries in UPT Sunan Kalijaga State Islamic University Library. Background of this research is because the UPT Library of the State Islamic University (UIN) Sunan Kalijaga is one of the tertiary libraries that have disabled users, both undergraduate and graduate students. In order to guarantee the right of disabled user of the service, the International Federation of Library Associations Standards are realized in the field of accessibility of services for people with disabilities. Keywords: disabilities, library inclusion